The Use of Total Physical Response in Teaching Vocabulary Integrated with Meaningful Classroom Interaction - Baiq Sumarni; Dharma Dev Bhatta; Sharon Fung-Chien Kho (Journal of Language and Literature Studies, 2022)
The deep consideration in teaching vocabulary is promosing a deep level of processing that can involve either long-term or short-term memory. This study was aimed at investigating the use of total physical response in the teaching of vocabulary integrated with meaningful classroom interaction. To attain the research aim, this study employed classroom action research. The steps of classroom action consisted of Planning, Acting, Evaluating and Reflecting. In the planning phase, researchers prepared lesson plans in line with students’ vocabulary problems and mastery. The students’ vocabulary problems were determined on how their solutions were before applying it in the class. The phase of the Acting is the session of applying total physical response as learning activities to improve students’ vocabulary. The acting activities should be done in accordance with the previous plan prepared. The last but not least is evaluating and reflecting. It referred to the evaluation process since researchers applied the learning strategies in the class. The upcoming process is then reflection, and it is emphasized on whether the learning plans are on the track. This study was carried out in middle schools. The sample was chosen by using purposive sampling technique. 37 students in the eleventh-grade class were involved in this study. The successful criteria were enacted in 75, and the indicators covered expanding word knowledge, adding specific words, word-learning strategies, and word-play activities. Based on the analysis result, students were able to conduct various learning activities to improve wide and extensive independent reading activities to expand their word acquisition and knowledge; students were able to perform meaningful strategies relating to specific words to improve their comprehension of texts containing those words; students were able to perform word-play activities to improve learning atmospheres in the class. Therefore, it can be concluded that the use of total physical response was able to improve students’ vocabulary mastery in integration with meaningful classroom interaction. The implementation of this strategy with paying attention to classroom interaction is strongly recommended to be applied for other language elements.